Addressing The Post Covid-19 Economic Consequences Of Lockdown In India - et. al., Dr. Vijay D. Joshi , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
On account of the national closedown, the economy has suffered a severe slump. The reduced purchase of goods and services has lead to slow down of domestic manufacturing and agricultural sectors, leading to severe unemployment in urban industrial areas and contraction of the rural economy. This lockdown has influenced economy and business circumstance in India as it has occurred in other nations. The ongoing lockdown due to COVID-19 outbreak affects the Indian economy in many ways, including sharp declines in domestic demand, lower tourism and business travel, trade and production linkages, supply disruptions, and health effects. There are certain sectors that have been affected due to the outbreak of corona virus. This research paper, anticipates indicative measures that may be taken to revive the economy as well as affected sectors to some extent. First, this paper provides an overview of effect of this lockdown on Indian economy. With no manufacturing activity, it is likely that growth of gross domestic product (GDP) will be slowed down. This will be followed listing of the sectors affected due to COVID-19, which carries the risk of global supply chain disruptions. This includes five import items that are heavily dependent on China - electrical machinery, mechanical appliances, organic chemicals, plastics and surgical instruments – that make up about 28% of India’s import basket could be the mostly affected ones due to this potential shutdown. Next, the paper will present some of the indicative measures to revive the economy and rejuvenate the affected sectors. Protection of workers at the workplace must be given utmost priority followed by adapting to new work arrangements such as work-from-home (WFH). This will be followed by measures to stimulate the economy and labour demand by making and implementing active fiscal policy. Making expenditure on purchasing domestic goods and services will be the best way to push the economy. As a matter of fact, it is now may be required to evaluate on what can be produced here (in India) and give a deliberate thought to it towards implanting the same. Further, India will be at advantage by having domestically based and well established ‘pharma industry’. This sector may act as ‘catalyst sector’ towards economic growth of the country.